Application of Solar Energy Bank as a Energy Source for Fisherman Community - Supu, Idawati; Ahmadi, Haerul; Latief, Muh. Fachrul (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Lopo is one of the village in Batudaa Pantai District and the center of the communitys socio economic activities. The major source of livelihood for the people in Loopo Village is by utilizing local potential in the coastal area so that majority of the fisherman with category of living below the poverty line. Thus, a literature review was carried out to suumarize stages and processes for developing coastal economic potential and environmental management as well optimizing creative economic potential as an effort to improve quality of life for the coastal communities of Lopo Village, which includes the use of advanced materials recharge energy bank was made from silicon solar panel. The results program was a form installation of solar energy bank 220 Voltage that can be used by fisherman. The society had used continuously which the product was a result by this program. This tool is very useful for fishing activities at sea at night because it is a lighting tool to replace the flashlights that fishermen have been using.